A millisecond structured illumination microscope for super-resolution live cell imaging. (19th March 2020) - Suzuki, Tomu; Kajimoto, Shinji; Kitamura, Narufumi; Takano-Kasuya, Mayumi; Furusawa, Naoko; Nakano, Yasushi; Fukumura, Hiroshi; Gonda, Kohsuke; Nakabayashi, Takakazu
Abstract: In typical super-resolution microscopy, high temporal resolution is sacrificed to achieve a spatial resolution beyond the diffraction limit. In this study, we have developed a new structured illumination microscopy (SIM) system using two Pockels cells, achieving a temporal resolution of 1 ms. The introduction of the two Pockels cells enables control of the phases of the illumination pattern along the X - and Y -axes in microseconds. We obtained five images consecutively with different illumination patterns and reconstructed a super-resolution image. We observed fluorescent nanoparticles in living cells for 8 s with super resolution and a frame rate of 1, 000 fps.